2019
DOI: 10.1504/ijesb.2019.101104
|View full text |Cite
|
Sign up to set email alerts
|

Roles of career anchors and path dependency in the entrepreneurial process: case Finland

Abstract: Studies of entrepreneurship education emphasise the impact of this educational process in career and entrepreneurship development. This study focuses in particular on the impact of the decision to start entrepreneurship education at the university level. Traditionally, career anchors are associated with relatively stable career development, but through an analysis of 59 life stories, this research observed that career anchors are more flexible. This study revealed four main types of previous life paths among t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
(75 reference statements)
0
1
0
Order By: Relevance
“…As for the deficiencies, the main points include two: the first is on the assumption that the individuals can rationally understand all information that the region owns, so they can always make the right choice to enter into and form an agglomeration; and the second is that prior research is mostly rooted on empirical study based on static data, which always build the connections between the new entrants and existing entrepreneurial agglomeration, while ignoring the trajectory of agglomeration formation process. Theoretically, if the individuals can make use of the economic and social advantages fully under the assumption of information transparency or effects of path-dependency [ 59 ], entrepreneurship will always be reinforced and the increasing return to entrepreneurship will hold on continuously [ 60 ], which will result in the region’s long-time sticky to all potential entrepreneurs and finally keep on growing in its agglomeration. However, our cases in the first section have demonstrated that this argument cannot be supported.…”
Section: Literature Review and The Basic Modelmentioning
confidence: 99%
“…As for the deficiencies, the main points include two: the first is on the assumption that the individuals can rationally understand all information that the region owns, so they can always make the right choice to enter into and form an agglomeration; and the second is that prior research is mostly rooted on empirical study based on static data, which always build the connections between the new entrants and existing entrepreneurial agglomeration, while ignoring the trajectory of agglomeration formation process. Theoretically, if the individuals can make use of the economic and social advantages fully under the assumption of information transparency or effects of path-dependency [ 59 ], entrepreneurship will always be reinforced and the increasing return to entrepreneurship will hold on continuously [ 60 ], which will result in the region’s long-time sticky to all potential entrepreneurs and finally keep on growing in its agglomeration. However, our cases in the first section have demonstrated that this argument cannot be supported.…”
Section: Literature Review and The Basic Modelmentioning
confidence: 99%
“…Therefore graduates of educational institutions must be directed to become entrepreneurs, and the cultivation of an entrepreneurial spirit must start from the basic education level. Education is able to foster an entrepreneurial spirit, even in developed countries including entrepreneurship education in the curriculum (Rusko, Hietanen, Kohtakangas, & Järvi, 2019) (Khairani, 2018)(Zaryab & Saeed, 2018. They realize that economic progress is only by training its citizens to be entrepreneurs, and being able to create their own jobs, and can even absorb other workers, unemployment will decrease.…”
Section: Introductionmentioning
confidence: 99%
“…Efforts to reduce unemployment in a country is to create jobs through the development of entrepreneurship (Baluku & Otto, 2019) Entrepreneurship education is able to foster an entrepreneurial spirit. (Stout & Annulis, 2019)(Zaryab & Saeed, 2018 (Rusko et al, 2019) Entrepreneurship today is generally oriented to business profits, without thinking about the environmental impact left behind. In fact, because they are only pursuing profits for the owners of capital, they do not care about the environmental damage that occurs, such as soil, water and air pollution, environmental destruction, depletion of forests so that the potential for flash floods threatens many areas in Indonesia.…”
Section: Introductionmentioning
confidence: 99%